Penerapan Self-Reparenting Siswa untuk Peningkatan Karakter Kemandirian Belajar di SMP dan SMA Negeri Tarakan - Siti Rahmi; Siti Sulistyani Pamuji; Romlah Ulfaika; Rita Kumala Sari; Eva Apriani; Saiful Saiful (Postgraduate, University of Mataram, 2024)
This research aims to find the level of student independence through the application of self-repairing. In the context of the learning process, it can be seen that there is a phenomenon of students who are less independent in learning and have bad habits in studying, such as: not feeling comfortable studying for a long time, studying only before exams, and so on. One of the learning processes towards independence is by helping students through self-reparenting. Self-repairing is a process of re-nurturing oneself, so that someone is able to make the choice to prioritize the positive and ignore the negative, so that they have a feeling of success and there will be change in the student. The research method used is an experimental method with a quantitative research type. The measurement process on subjects was carried out at the stage before treatment (Pre-test) and after treatment (post-test) using a Likert scale as a data collection tool. Based on the results of the hypothesis test, it can be concluded that there is an increase in students' independent learning character. This can be seen in table 5, it can be seen that the df value is 35 and the significant value is 0.000 < 0.05, meaning it is significant or accepted. Then in table 7, it is known that the df value is 29 and the significant value is 0.000 < 0.05, meaning it is significant or accepted. This shows that classical services with self-reparenting techniques can improve the independent learning character of students in Tarakan State High Schools and Middle Schools